2009
DOI: 10.1364/oe.17.020700
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber CARS microscopy of live cells

Abstract: Using an all-fiber laser system consisting of a femtosecond Er/Yb fiber oscillator as the pump and an ultra-highly nonlinear fiber for Stokes generation, we demonstrate multimodal (TPF+SHG+CARS) non-linear optical microscopy of both tissue samples and live cells. Multimodal imaging was successfully performed with pixel dwell times as short as 4 micros at low laser powers (< 40 mW total).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…Therefore, toward the goal of coupling the CARS imaging modality to other widely used platforms of multiphoton microscopy, Pegoraro et al ( 38 ) and Chen et al ( 39 ) showed independently high-speed CARS imaging of lipids with femtosecond (fs) laser pulses. Commercial CARS microscopes with either ps or fs laser sources are now available through Leica and Olympus, respectively.…”
Section: Coupling Cars Imaging With Spontaneous Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, toward the goal of coupling the CARS imaging modality to other widely used platforms of multiphoton microscopy, Pegoraro et al ( 38 ) and Chen et al ( 39 ) showed independently high-speed CARS imaging of lipids with femtosecond (fs) laser pulses. Commercial CARS microscopes with either ps or fs laser sources are now available through Leica and Olympus, respectively.…”
Section: Coupling Cars Imaging With Spontaneous Raman Spectroscopymentioning
confidence: 99%
“…Furthermore, the integration of spontaneous Raman spectroscopy onto the CARS microscope platform provides complete high-resolution Raman spectral information of the samples ( 47 ). Compact laser sources ( 38,117,118 ) are being developed to make CARS microscopy more accessible to biomedical researchers by reducing its cost, footprint, and complexity. Increasing the penetration depth with CARS endoscopy ( 84,85 ) or miniature microscope objective ( 119 ) could allow CARS imaging from the lumen of the intestine, esophagus, and artery, or CARS imaging of lipid-rich tissues with minimally invasive surgery.…”
Section: Study Of Myelin Diseasesmentioning
confidence: 99%
“…Attenuated peaks were observed at 2870, 2910 and 2950 cm -1 , which were attributed to lipid phase changes and changes in protein content. Pegoraro et al (2009b) recently demonstrated a novel spectral focusing implementation to acquire high resolution CARS spectra in the C--H stretching vibration region, using an optimally chirped multimodal CARS microscopy based on a single femtosecond Ti:sapphire laser and synchronized PCF output. Preliminary data showed that clear spectral differences could be detected from multiple regions of interest identified in a rabbit artery section.…”
Section: Broadband Cars Imagingmentioning
confidence: 99%
“…With the improved power distribution, an enhanced CARS signal can be achieved when using PCF 5 i.e. a faster imaging process than achieved with other PCF based CARS systems (4 µs/pixel) [16]. Note that the commercially available fiber is not polarization maintaining.…”
Section: Optimum Pcf For Carsmentioning
confidence: 99%
“…Previously, CARS setups using PCF for generation of the Stokes wavelength have been presented [15,16]. However, wavelength conversion to the relevant IR wavelength was weak.…”
Section: Introductionmentioning
confidence: 99%